2022
DOI: 10.1039/d2nr05653d
|View full text |Cite
|
Sign up to set email alerts
|

Highly luminescent dual-phase CsPbBr3/Cs4PbBr6 microcrystals for a wide color gamut for backlight displays

Abstract: Cesium lead bromide perovskite nanocrystals (NCs) embedded in Cs4PbBr6 or CsPb2Br5 matrices forming a core/shell structures are promising luminescent materials that exhibit remarkable photoluminescence properties meeting a wide range of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…In our recent report on the CsPbBr 3 -Cs 4 PbBr 6 composite, it has been shown that green emission originated from the CsPbBr 3 NCs and that Cs 4 PbBr 6 , with its large band gap, passivated the surface defects of the CsPbBr 3 NCs, helping achieve high PLQY and better long-term stability. 22 Thus, the findings from TEM, XRD, and Raman analyses, demonstrating the transformation in morphology and crystal structure are in accordance with the changes observed in absorption and emission spectral profiles. In light of the above results, the following discussion delves into the phase transition occurring from the cubic CsPbBr 3 to hexagonal Cs 4 PbBr 6 NCs, as the ZnBr 2 doping content in CsPbBr 3 increases.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In our recent report on the CsPbBr 3 -Cs 4 PbBr 6 composite, it has been shown that green emission originated from the CsPbBr 3 NCs and that Cs 4 PbBr 6 , with its large band gap, passivated the surface defects of the CsPbBr 3 NCs, helping achieve high PLQY and better long-term stability. 22 Thus, the findings from TEM, XRD, and Raman analyses, demonstrating the transformation in morphology and crystal structure are in accordance with the changes observed in absorption and emission spectral profiles. In light of the above results, the following discussion delves into the phase transition occurring from the cubic CsPbBr 3 to hexagonal Cs 4 PbBr 6 NCs, as the ZnBr 2 doping content in CsPbBr 3 increases.…”
Section: Resultssupporting
confidence: 79%
“…The GSB is due to the reduction of ground-state ions caused by band-edge filling, while PA is observed at lower and higher excitation states, labeled as PA1 and PA2, respectively. 22,48 TA spectra of CsPbBr 3 and 60% ZnBr 2 -doped PNCs exhibit sharp ground bleach signals at around 512 nm because of a reduction in the quantity of ground-state ions caused by band-edge filling and positive photo-induced absorption bands (PA1 and PA2) at around 484 and 539 nm, respectively. The spectral features of both PNCs are similar, but the bleach recovery signals of the Zn-doped PNCs are slower than those of the pristine PNCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is nearest to the NTSC 2020 (98%) (Table S2, ESI†). From Table S3 (ESI†), the color gamut space of the LD driven backlight panel is wider than that of the other reported works, 45–52 which is the highest one so far. Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Therefore, the CsPbBr 3 /Cs 4 PbBr 6 composite structure prepared in this work provides a larger optical band gap compared to that of the bulk material. According to the accepted theory in semiconductor QDs, this blueshift of the absorption edge from 540 to 525 nm is attributed to quantum confinement enhancement …”
Section: Resultsmentioning
confidence: 94%